Downstream Economic Implications of Predation in the South African Red Meat Industry - van Niekerk, Hermias N.; Bahta, Yonas T.; Maré, Frikkie A. (Frontiers in Sustainability, 2022)
Globally, predation is an important and ongoing problem facing the livestock sector. This study estimated the downstream economic impact of predation in the South African red meat industry using a recent South African Social Accounting Matrix (SAM) and a partial equilibrium model. Due to predation the total output decreased by R 3,806 million and R 648 million for large (cattle) and small livestock (sheep and goat), respectively. The result implies that the loss of livestock due to predation reduces the number of livestock available for marketing and the presence of predators influences the level and intensity of best management practices employed by the red meat industry. The findings of this study, which looked at the macroeconomic implications of predation in the South African red meat industry, as well as the biodiversity and ecology aspects of predation, could help government and policymakers develop appropriate policies and mitigation strategies to reduce prediction and prioritize strategies that will help lessen the impact of predation.